Affirmative Action for Women’s Representation in Legislative Elections: Case Study of the 2024 General Election in Tarakan City - Anggita, Putri; Firmantoro, Zuhad Aji (Journal La Sociale, 2024)
The aim of this research is to provide views regarding women’s representation in legislative general elections by taking the election case in Tarakan City. This type of legal research is Normative Empirical, in terms of combining Normative elements such as study material from legal regulations that are valid in writing and supported by the addition of data or Empirical elements. Based on the research results, three conclusions were found, namely first, the regulation of women’s participation in nominating legislative members has been regulated in Law Number 7 of 2017 concerning General Elections, second, in the Permanent Candidate List all political parties have sufficient quota of 30% but the election results are only there are 6 (six) female Legislative Candidates elected from 25 seats in the Tarakan City DPRD, thirdly, even though they have fulfilled the 30% quota on the Permanent Candidate List, political parties must pay more attention to the cadre formation of women within the party so that the issue of women’s involvement is no longer just a matter of quantity but also about quality.